A pedagogia de projetos na práxis da educação ambiental: uma experiência na Escola Agrotécnica Federal de Uberlândia, MG, 2003-2004 - Valéria G. de Freitas Nehme; Marlene T. Muno Colesanti (Sociedade & Natureza)
We set the following objectives for the realization of the research: to study the contributions ofpedagogical projects in the praxis of Environmental Education for the training of technicians inenvironment from Federal Agrotechnical School of Uberlândia; to analyze the pertinence of peda-gogical projects in the training of technicians in environment, who will serve as agents of Environ-mental Education in the institution of learning itself; to verify how work offers with EnvironmentalEducation projects determines a character transformation in student practices; to diagnose pro-duction potential of related knowledge as to local questions (productive and pedagogical sectorsof the School) and the participation/intervention in this reality; to evaluate the results of this practice, offering contributions for future work of Environmental Education in the FederalAgrotechnical School of Uberlândia and other institutions of learning. We applied research/action to carry out projects of Environmental Education, since this methodology establishes closeassociation with an action or with the solution of collective problems and with which, researchersand participants are involved in a cooperative and/or participative way.